Toward a shared urban transport system passengers & Goods Cohabitation - Trentini, Anna; Mahléné, Nicolas (TeMA - Journal of Land Use, Mobility and Environment, 2011)
The paper presents radical new urban transportation system concepts, potentially allowing changing the economic and environmental costs of passenger and freight transportation. The driver focuses on the concept of sharing, which means to make a joint use of transport resources, between passengers and goods flows. From a field observation of several existing solutions, an inductive reasoning enables us to move from a set of specific facts to establish an archetype for a radical new urban transportation system. Once the archetype defined, it is translated in real life through the example of the On Route proposal for London. The research frame of this paper is the ANR ( French National Research Agency) C-Goods (City Goods Operation Optimization using Decision support System) project. Started in February 2009 the project involves four partners, (The multi-disciplinary French engineer school EIGSI (Ecole d’Ingénieurs en Génie des Systèmes Industriels), the French university ENMP (Ecole Nationale Supérieure des Mines de Paris), the Poitiers Urban Community (CAP), and the consulting service Interface Transport, specialized in transport economy) and will end on 2012.